Effect of Potassium Channel Modulators on Morphine Withdrawal in Mice - Vikas Seth; Mushtaq Ahmad; Prerna Upadhyaya; Monika Sharma; Vijay Moghe (SAGE Publishing, 2010)
The present study was conducted to investigate the effect of potassium channel openers and blockers on morphine withdrawal syndrome. Mice were rendered dependent on morphine by subcutaneous injection of morphine; four hours later, withdrawal was induced by using an opioid antagonist, naloxone. Mice were observed for 30 minutes for the withdrawal signs ie, the characteristic jumping, hyperactivity, urination and diarrhea. ATP-dependent potassium (K + ATP ) channel modulators were injected intraperitoneally (i.p.) 30 minutes before the naloxone. It was found that a K + ATP channel opener, minoxidil (12.5-50 mg/kg i.p.), suppressed the morphine withdrawal significantly. On the other hand, the K + ATP channel blocker glibenclamide (12.5-50 mg/kg i.p.) caused a significant facilitation of the withdrawal. Glibenclamide was also found to abolish the minoxidil's inhibitory effect on morphine withdrawal. The study concludes that K + ATP channels play an important role in the genesis of morphine withdrawal and K + ATP channel openers could be useful in the management of opioid withdrawal. As morphine opens K + ATP channels in neurons, the channel openers possibly act by mimicking the effects of morphine on neuronal K + currents.